Untargeted metabolomics in Anectocillus roxburghii with habitat heterogeneity and the key abiotic factors affecting its active ingredients - Lyu, Xinkai; Diao, Haixin; Li, Jiaxue; Meng, Zhixia; Li, Bing; Zhou, Lisi; Guo, Shunxing (Frontiers in Plant Science, 2024)
Anoectochilus roxburghii is a rare, endangered herb with diverse pharmacological properties.Understanding the main metabolite types and characteristics of wild A. roxburghii is important for efficiently utilizing resources and examining quality according to origin. Samples were collected from five regions in the main production area of Fujian Province, China. Untargeted metabolomics analysis was conducted on the entire plants. A total of 3,170 differential metabolites were identified, of which terpenoids and flavonoids were the most abundant. A region-specific metabolite analysis showed that YC presented the highest number of unique metabolites, including tangeretin and oleanolic acid, while YX had the least, with only one distinct metabolite. KEGG pathway enrichment analysis indicated significant enrichment in the flavonoid biosynthesis pathway. Further examination of the flavonoids revealed that flavonols exhibited the highest differential abundance. UPLC-MS/MS was used to quantify eight targeted flavonoids, showing that the YX region generally exhibited higher flavonoid levels. Correlation analysis highlighted a significant association between flavonoids and habitat, especially temperature and humidity. In conclusion, untargeted metabolomics via LC-MS was suitable for identifying region-specific metabolites and their influence via habitat heterogeneity. The results of this study serve as a new theoretical reference for unique markers exclusively present in a specific sample group.